Triphenylbismuth carbonate-mediated oxidation of hydroxylamines to nitrones and in situ 1, 3-dipolar cycloaddition. Issue 92 (19th September 2016) - Nguyen, Dinh-Vu; Prakash, Praveen; Gravel, Edmond; Doris, Eric
Abstract : Triphenylbismuth carbonate was shown to act as a mild, selective and efficient reagent for the oxidation of hydroxylamines. Abstract : Triphenylbismuth carbonate was shown to act as a mild, selective and efficient reagent for the oxidation of hydroxylamines. The developed reaction conditions were shown to be compatible with the in situ trapping of the produced nitrones by a strained alkyne, via a [3 + 2] cycloaddition reaction.